2011
DOI: 10.5301/jbm.2011.8872
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of C-Reactive Protein in Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: CRP has a critical prognostic value in patients with breast cancer as an inflammation biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 31 publications
2
65
1
1
Order By: Relevance
“…CRP is increased in the circulation in response to acute inflammation, infection and tissue damage. Studies reporting a higher level of CRP in breast carcinoma cells claimed that elevated CRP levels were associated with an increased risk of breast cancer (29) or had a prognostic value in patients with breast cancer (30). By contrast, the present study indicates that the cancer state in the body increases CRP levels to fight against tumor cells.…”
Section: Discussioncontrasting
confidence: 53%
“…CRP is increased in the circulation in response to acute inflammation, infection and tissue damage. Studies reporting a higher level of CRP in breast carcinoma cells claimed that elevated CRP levels were associated with an increased risk of breast cancer (29) or had a prognostic value in patients with breast cancer (30). By contrast, the present study indicates that the cancer state in the body increases CRP levels to fight against tumor cells.…”
Section: Discussioncontrasting
confidence: 53%
“…Currently, there is a strong evidence for the elevated levels of CRP in patients with chronic infections and autoimmune diseases [7][8][9]. In addition, elevated levels of CRP had been found in patients with cancers [9][10][11][12]15]. Previous studies also showed that elevated levels of CRP were associated with decreased survival and increased risk of mortality in various cancers [16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 92%
“…Currently, there is a strong evidence for important roles of CRP in the development of chronic infections and autoimmune diseases [7,8]. Previous studies suggest that patients with cancer often have increased levels of circulating CRP, and increased level of serum CRP has been proven to be an important prognostic factor in several types of cancers including colorectal cancer and breast cancer [9][10][11]. However, the prognostic significance of serum CRP level in patients with osteosarcoma was still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Poorer prognosis in cancer patients, including those of breast cancer was also reported (1,14), but evidence on the association of CRP with breast cancer risk is inconsistent. The association may also differ by degree of body adiposity.…”
Section: Introductionmentioning
confidence: 99%